Answer :



taking LCM



3x2 + 2x - 1 = 14x - 10 cross multiplying


3x2 - 12x + 9 = 0 taking 3 common


x2 - 4x + 3 = 0


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 1 b = - 4 c = 3


= 1.3 = 3


And either of their sum or difference = b


= - 4


Thus the two terms are - 3 and - 1


Sum = - 3 - 1 = - 4


Product = - 3. - 1 = 3


x2 - 4x + 3 = 0


x2 - 3x - x + 3 = 0


x(x - 3) - 1(x - 3) = 0


(x - 3) (x - 1) = 0


(x - 3) = 0 or (x - 1) = 0


x = 3 or x = 1


Hence the roots of equation are 3 or1.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses